2017
DOI: 10.3390/nu9040353
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A Oral Supplementation Induces Oxidative Stress and Suppresses IL-10 and HSP70 in Skeletal Muscle of Trained Rats

Abstract: Exercise training intensity is the major variant that influences the relationship between exercise, redox balance, and immune response. Supplement intake is a common practice for oxidative stress prevention; the effects of vitamin A (VA) on exercise training are not yet described, even though this molecule exhibits antioxidant properties. We investigated the role of VA supplementation on redox and immune responses of adult Wistar rats subjected to swimming training. Animals were divided into four groups: seden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 66 publications
(85 reference statements)
2
17
0
Order By: Relevance
“…Fat-soluble vitamins (A, D, E, and K) have been evaluated for their potential effects on GSH homeostasis. These vitamins exhibit antioxidant properties, and there is evidence that status of vitamin A [116,117], vitamin D [118,119,120], and vitamin K [121] may affect GSH levels; supplementation has also been associated with adverse effects [117]. Given the nature of this review, we will focus on the fat-soluble vitamin that directly affects GSH concentrations through its antioxidant capabilities: vitamin E.…”
Section: Effects Of Micronutrient Supplementationmentioning
confidence: 99%
“…Fat-soluble vitamins (A, D, E, and K) have been evaluated for their potential effects on GSH homeostasis. These vitamins exhibit antioxidant properties, and there is evidence that status of vitamin A [116,117], vitamin D [118,119,120], and vitamin K [121] may affect GSH levels; supplementation has also been associated with adverse effects [117]. Given the nature of this review, we will focus on the fat-soluble vitamin that directly affects GSH concentrations through its antioxidant capabilities: vitamin E.…”
Section: Effects Of Micronutrient Supplementationmentioning
confidence: 99%
“…Many other substances such as resveratrol, melatonin, vitamin A, lutein, zeaxanthin, etc. ( Kubota et al, 2009 ; Bian et al, 2012 ; Tian et al, 2013 ; Petiz et al, 2017 ; Tuzcu et al, 2017 ) have shown antioxidant and anti-inflammatory properties in the retina and in other tissues. However, the relation between antioxidant therapy and inflammatory diseases needs more study.…”
Section: Discussionmentioning
confidence: 99%
“…Yew et al made a comprehensive summary of the potential mechanisms by which vitamin A could play a role in TB reactivation and also mentioned controversies in the literature on the pro-or antioxidative effects of vitamin A (2). In the studies that they referenced, the antioxidative effect of vitamin A has been demonstrated in humans and mice (6, 7), whereas studies conducted using rat models showed that vitamin A supplementation enhanced oxidative stress (8,9). Whether the differential effect in the pro-or antioxidative properties of vitamin A lies in the different metabolic pathways in different organisms, the different dose administered in various studies, or the different tissues examined (e.g., serum, organ, skeletal muscle) remains to be elucidated.…”
Section: The Authors Replymentioning
confidence: 99%